2017
DOI: 10.4322/2526-8910.ctoao0992
|View full text |Cite
|
Sign up to set email alerts
|

Método self-healing como estratégia de promoção à saúde e reabilitação de pessoas com esclerose múltipla no contexto da terapia ocupacional

Abstract: Resumo: Introdução: A esclerose múltipla, doença neurológica crônica, de evolução contínua e diferenciada, demanda autoconhecimento do corpo, para melhor percepção das capacidades preservadas, das perdas gradativas e da repercussão na realização das atividades e na participação social. Objetivo: Analisar a experiência grupal de aplicação das técnicas corporais baseadas no método self-healing, para a promoção da saúde e reabilitação de pessoas com esclerose múltipla, desenvolvida pela terapia ocupacional. Métod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 4 publications
(5 reference statements)
0
3
0
2
Order By: Relevance
“…A prática do exercício físico é uma grande alternativa para a promoção da saúde, reabilitação e responsabilidade da pessoa pelo cuidado à saúde, como sugerido pelas políticas da saúde. Isso explica a importância do desenvolvimento de futuros estudos sobre a temática por meio da terapia ocupacional (Pimentel;Toldrá, 2017).…”
Section: Métodounclassified
“…A prática do exercício físico é uma grande alternativa para a promoção da saúde, reabilitação e responsabilidade da pessoa pelo cuidado à saúde, como sugerido pelas políticas da saúde. Isso explica a importância do desenvolvimento de futuros estudos sobre a temática por meio da terapia ocupacional (Pimentel;Toldrá, 2017).…”
Section: Métodounclassified
“…The application of these techniques stimulates and balances the organic, physical, psychological functions in a harmonious way, as it allows the development of a dialog between the body, the mind, the emotions, and the sensations. 50 It has been shown that health promotion programs in stress management, fitness, nutrition, weight control, and selfmedication improve health conditions; however, the impact on self-healing among people with acute and chronic diseases has also been shown to be mixed. 51 Self-healing in the context of acute and recurring musculoskeletal pain is the innate process of the body and mind, to promote body networks to return to equilibrium and relieve pain.…”
Section: Self-healing Conceptmentioning
confidence: 99%
“…The fourth category of Group Intervention (BROWN et al, 2016;TOLDRÁ, 2017aTOLDRÁ, , 2017b showed the importance of group development as a space for sharing experiences, helping and expanding the social network support, and the specific benefits pointed out by each of the authors.…”
Section: Vocational Rehabilitationmentioning
confidence: 99%
“…The study highlighted that the content and group process need to reflect the complexity of relearning to live with cognitive impairment, a process with several interrelated phases that includes the restoration of personal identity and relationships (BROWN et al, 2016). Pimentel and Toldrá (2017a) also analyzed the group experience using body techniques based on the self-healing method. The first moment of the session focused on the triggering questions that guided the conversations and the exchange of experiences.…”
Section: Vocational Rehabilitationmentioning
confidence: 99%